Studi Eksperimen Variasi Temperatur Masuk Air Pendingin Terhadap Kinerja Prototype Shell And Tube Aliran Berlawanan Arah - Azmain Noor Hatuwe; Jeffrie J Malakauseya; Dwi Rendi Saputra Latuconsina (Department of Mechanical Engineering, 2026)
Advancements in technology and heat transfer systems necessitate heat exchangers that meet industrial requirements. Heat exchangers play a crucial role in heat transfer; the counter-flow type, in particular, is widely used due to its superior heat transfer capabilities. This study investigates the effect of varying the inlet temperature of the cold fluid on heat exchanger performance. The cold fluid inlet temperature (Tc,in ) was varied specifically at 20.9°C, 23.3°C, 25.1°C, 28.2°C, 30.4°C, and 32.2°C as the independent variable, while total energy and the overall heat transfer coefficient served as the dependent variables. The results indicate that increasing the initial temperature of the cooling water entering the exchanger leads to a rise in the cooling water temperature and a decrease in the outlet temperature of the hot fluid; notably, the overall heat transfer coefficient (U) increased from 672.71 W/m²°C to 852.74 W/m²°C. Regarding total heat transfer energy, the total energy released was 9,414 J/s during the first test (initial temperature of 20.9°C) and 8,451.68 J/s during the fifth test (initial temperature of 30.4°C), representing a decrease of 962.68 J/s in released energy. Both the exchanger effectiveness and the NTU value tended to increase; the first test yielded effectiveness and NTU values ​​of 0.46 and 2.25, respectively, while the final test resulted in values ​​of 0.54 and 2.85. The increase in NTU was driven by the rise in the overall heat transfer coefficient (U), while the increase in effectiveness was influenced by the rise in the NTU value. Keywords: Heat Exchanger, Flow Rate, Heat Transfer